Study guide [for] business statistics for management and economics - Daniel, Wayne W., 1929-; Terrell, James C. (Geneva, Ill. : Houghton Mifflin, 1995)
Introduction to business statistics. Organizing and summarizing data. Some elementary probability concepts. Some important probability distributions. Some important sampling distributions. Statistical inference I, II. Analysis of variance...
Keywords: Statistics; Commercial statistics; Social sciences; Statistical methods; Statistics; Social sciences -- Statistical methods; Commercial statistics